Penyelesaian Nonpenal Tindak Pidana Kekerasan dalam Rumah Tangga di Wilayah Hukum Kepolisian Resor Batanghari - Nurhasan Nurhasan (Universitas Batanghari Jambi, 2022)
Domestic violence that occurs in the family and victims of domestic violence also do not want to report violence that occurs in their families, so victims prefer to hide the violence that occurs in their families. To protect victims of domestic violence from perpetrators, the government makes laws and regulations. The type of research in this research is empirical juridical which is carried out directly to the Batanghari Resort Police office with descriptive research specifications. Sources of data are field research and literature. Considering that the research uses an empirical juridical type, the approach used in this research is a sociology of law approach with data collection techniques using interviews and qualitative data analysis. Thus, the results of the study are the non-penal settlement of criminal acts of domestic violence in the jurisdiction of the Batanghari Resort Police, namely that non-penal applications have been carried out on perpetrators and newspapers of domestic violence by means of mediation which is directly carried out by the Head of the Women and Children Service Unit as a mediator. The obstacle faced in carrying out non-penal settlements of criminal acts of domestic violence in the jurisdiction of the Batanghari Resort Police is the minimum number of personnel in the Women and Children Service Unit and there is no special place for non-penal settlements at the Batanghari Resort Police.